Exploring the Infectious Drug Target Glutathione S-Transferase in Plasmodium falciparum with the Inhibitory Potential of Azadirachta indica Phytocompounds - Esam S. Al-Malki (Advances in Public Health)
Background. Neem compounds are being studied for their potential as new and effective antimalarial drugs, and there is mounting evidence that they may help treat malaria. The PfGST enzyme is crucial to the malaria parasite’s survival, making it a desirable target for new antimalarial drugs, and the study aims to examine the bark region compounds as PfGST inhibitors. Methods. The structure of PfGST is examined for quality analysis, the active site is predicted based on a web server, and the bark region compounds are docked for their binding potential. Final molecules are identified for the absorption, distribution, metabolism, and excretion (ADME) analysis to confirm the possible future leads that target malaria. Results. This study reports that IMPHY000093, IMPHY001448, and IMPHY005310 can be potential inhibitors, showing strong binding potential in hydrogen bonds, scoring values, and ADME analysis. Results are confirmed by the possible re-docking poses by the docking method, and the binding score is used for the evaluations. Conclusion. Neem’s active ingredients have shown promise as a new class of antimalarial medications. Neem compounds may boost the efficacy of other antimalarial drugs and the host immune system by inhibiting GST, which is involved in the metabolism of the malaria parasite.